Touch-Sensing Input Devices - Hinckley, Ken; Sinclair, Mike (CHI '99 Proceedings of the SIGCHI conference on Human Factors in Computing Systems, 1999)
We can touch things, and our senses tell us when our hands are touching something. But most computer input devices cannot detect when the user touches or releases the device or some portion of the device. Thus, adding touch sensors to input devices offers many possibilities for novel interaction techniques. We demonstrate the TouchTrackball and the Scrolling TouchMouse, which use unobtrusive capacitance sensors to detect contact from the user's hand without requiring pressure or mechanical actuation of a switch. We further demonstrate how the capabilities of these devices can be matched to an implicit interaction technique, the On-Demand Interface, which uses the passive information captured by touch sensors to fade in or fade out portions of a display depending on what the user is doing; a second technique uses explicit, intentional interaction with touch sensors for enhanced scrolling. We present our new devices in the context of a simple taxonomy of tactile input technologies. Finally, we discuss the properties of touch-sensing as an input channel in general